Combating Cholera - Hsueh, Brian Y. (F1000Res, 2019)
Cholera infections caused by the gamma-proteobacterium Vibrio cholerae have ravaged human populations for centuries, and cholera pandemics have afflicted every corner of the globe. Fortunately, interventions such as oral rehydration therapy, antibiotics/antimicrobials, and vaccines have saved countless people afflicted with cholera, and new interventions such as probiotics and phage therapy are being developed as promising approaches to treat even more cholera infections. Although current therapies are mostly effective and can reduce disease transmission, cholera outbreaks remain deadly, as was seen during recent outbreaks in Haiti, Ethiopia, and Yemen. This is due to significant underlying political and socioeconomic complications, including shortages of vaccines and clean food and water and a lack of health surveillance. In this review, we highlight the strengths and weaknesses of current cholera therapies, discuss emerging technologies, and argue that a multi-pronged, flexible approach is needed to continue to reduce the worldwide burden of cholera.